MUSIC THERAPY AND SPIRITUAL TREATMENT TO REDUCE PAIN IN PATIENTS WITH SEVERE BURNS - Budiman, Ganjar Wisnu; Kosasih, Cecep Eli; Nuraeni, Aan (Universitas Aisyah Pringsewu, 2023)
Introduction:Pain is a problem experienced by patients with burns. Pain reduction is the main focus in the management of burn patients. Non-pharmacological treatment options with music therapy and spiritual care approaches are part of nursing care. Objective: The study was conducted to identify the effectiveness of music therapy and spiritual care in reducing pain during dressing changes for burn patients. Materials and methods:The study used a quasi experiment pre-post test method on 30 burn patients with the music therapy and other with spiritual care intervention. Samples were taken using accidental sampling. Patients were measured for pain level using Numeric rating scale (NRS). Data were analysed using univariate analysis, dependent t-test and an independent t-test to compare between music therapy and spiritual care. Result: Music therapy and spiritual care have a significant effect on the measurement results before and after the intervention resulting in a value of (P=0.000) p a (0.005). While the mean difference between music therapy and spiritual care after after dressing change (P=0.000) and (t=5.875). Conclusion: There is an effect of music therapy intervention and spiritual care on reducing pain in burn patients undergoing dressing change procedures. Spiritual care had a higher average reduction than music therapy.